Analisa Hubungan Grading Agregat Terhadap Kuat Tekan Dan Porositas Beton Porous Geopolimer - Darmoko, Wahyu Setyo; Qomaruddin, Mochammad; Saputro, Yayan Adi; Rochmanto, Decky; Roehman, Fatchur; Faqih, Nasyiin (Jurnal Teknik Sipil, 2025)
This research is an experimental study on porous concrete and the use of fly ash as a binder for concrete to analyze the effect of compressive strength and porosity. The research method used in this study is the experimental method which is a research method used to find the effect of certain treatments on concrete. In this research, the concrete mix design uses a ratio of gravel and geopolymer paste as a binder, namely 4: 1 and uses a molarity ratio of 10M with differences in grading of coarse aggregate using sieves number 4, 1/2 ", and 3/8". The optimum compressive strength value was obtained in mix design 1 using sieve gradation no.4 which was 4.25 MPa at 28 days old. While the results of the highest porosity value were found in mix design 1 which was 7.15% at 28 days old